A study on a simple and all-round GPS-based structure sonitoring system - Setan, Halim; Hang, Cheh Hang (2006)
Numerous accidents and disasters in the past have called for the need of structure to serve as an alarm or early-warning system. The monitoring could be categorised into normal (or non-urgent) and urgent monitoring schemes, depending on the case of monitoring, such as, the age and integrity of the monitored objects as well as the external load sustained by the monitored objects. This paper describes a GPS-based structure monitoring system, which is currently being developed at UTM, to undertake both normal and urgent monitoring survey. The normal monitoring scheme is performed as a regular check up when the monitored object is considered as healthy (or stable). In this case, the observations are preferentially carried out periodically and the results are obtained via post-processing (by using GPSAD2000). However, urgent monitoring scheme is performed when the stability status or integrity of the structure is questionable. Consequently, the online and continuous observation will be performed to provide the near real-time results. On the other hand, to serve the purpose of the study of structural dynamic response, other than providing the time-domain analysis, by using Fast Fourier Transform (FFT), the analysis could also be done in frequency domain. The research is the pilot study on the all-round GPS-based monitoring system.